The Mexican Third Sector of the Media: The Long Run to Democratise the Mexican Communication System - Rodrigo Gomez (tripleC: Communication, Capitalism & Critique)
This article addresses the structural historical conditions of the Mexican communication system (MCS) in relation to the process of its democratisation. In order to analyse this process of democratisation, the research focused on the struggles of the third sector of the media – citizen/community/popular/free/alternative/radical/indigenous – to find room in that communication system. The aim was to highlight the structural inequality faced by this sector when compared with the hegemony of the private/commercial – or first – sector. From a normative perspective, a democratic and pluralistic communication system must have fair and equitable conditions among the three media sectors – private, public and citizen – with the aim of generating horizontal public spheres as a plural network of spaces for public conversation and deliberation on common issues.